2015
DOI: 10.1007/s13369-015-1611-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Post-Treatment Techniques on Corrosion and Wettability of Hydroxyapatite-Coated Co–Cr–Mo Alloy

Abstract: This study is a comparison between the effect of sintering and alkaline post-treatment techniques on calcium phosphate-coated Co-Cr-Mo alloy in terms of electrochemical corrosion behavior and wettability. The Co-Cr-Mo substrates were electrophoretically coated by calcium phosphate in a solution of Ca(NO 3 ) · 4H 2 O and NH 4 H 2 PO 4 . The sintering and alkaline post-treatment techniques were then conducted to convert an as-deposited dicalcium phosphate dihydrate phase to crystalline hydroxyapatite (HA). The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…For example, in magnesium alloys, sintering post-treatment is not possible due to the low melting point of the substrate [832]. As an alternative, alkaline post-treatment is often used.…”
Section: Cap Coating Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in magnesium alloys, sintering post-treatment is not possible due to the low melting point of the substrate [832]. As an alternative, alkaline post-treatment is often used.…”
Section: Cap Coating Technologiesmentioning
confidence: 99%
“…Heat treatment, usually at 600–800 °C for 1 h, transforms the water trapped in the coating during deposition processes such as sputtering, ED, EPD and PS into ions, thus stabilizing the crystalline structure [ 49 ]. Shirdhar et al [ 832 ] investigated the influence of those two post-treatments on Co-Cr-Mo alloy EPD with CaP coating. XRD analysis confirmed that the majority of the DCPD phases initially deposited on the surface transformed to crystalline HAp after either sintering or alkaline post-treatment.…”
Section: Cap Coating Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The ANOVA table for the shape is presented in Table 3. Values less than 0.050 for 'Prob > F' indicate that the model is significant, which is desirable as it reveals that the terms in the model have a significant effect on the response [17,18]. The Model F-value of 16.50 implies that the model is significant.…”
Section: Analysis Of Variance (Anova) For Shapementioning
confidence: 99%
“…The morphology and structure of micro/nanosized biomedical materials also play a crucial role in their properties and applications [4,5]. Research has shown that a flake-like CaP coating on an alloy is beneficial for the improvement of osseointegration [6], and hydroxyapatite (HAp) nanorods can self-assemble to enamel-like structures [7] and sphere nano alginate/HAp that could promote bone mineral deposition [8]. However, most studies that have been reported have been based on the traditional trial and error method, namely the use of existing theoretical and empirical knowledge on materials, by adjusting the research material ratio, changing the reaction conditions, and performing characterization tests and inspections, in order to eventually obtain the required materials [9].…”
Section: Introductionmentioning
confidence: 99%